Carbonaceous aerosols contributed by traffic and solid fuel burning at a polluted rural site in Northwestern England - D. Liu; J. Allan; B. Corris; M. Flynn; E. Andrews; J. Ogren; K. Beswick; K. Bower; R. Burgess; T. Choularton; J. Dorsey; W. Morgan; et al. (Atmospheric Chemistry and Physics, 2011)
The experiment presented in this paper was conducted at the Holme Moss site, which is located in the southern Pennines region in Northwestern England during November–December 2006. The strong southwesterly wind during the experimental period, which enhanced the transport of urban pollutants from the conurbations of Greater Manchester and Liverpool, in addition to the seasonally increased nearby residential heating activities, made this site a receptor for pollutants from a range of sources. A factor analysis is applied to the mass spectra of organic matter (OM) measured by the Aerodyne Aerosol Mass Spectrometer (AMS) to attribute the pollutant sources. Besides the oxygenated organic aerosol (OOA), this site was found to contain a considerable fraction of primary organic aerosols (POA, mass fraction 50–70% within total mass of OM). The POA sources are attributed to be traffic emission and solid fuel burning, which are identified as hydrocarbon-like organic aerosol (HOA) and solid fuel organic aerosol (SFOA) respectively. There were strongly combined emissions of black carbon (BC) particles from both sources. The refractory BC component (rBC) was characterized by a single particle soot photometer. This site began to be influenced during the late morning by fresh traffic emissions, whereas solid fuel burning became dominant from late afternoon until night. A covariance analysis of rBC and POA was used to derive source specific emission factors of 1.61 μgHOA/μgrBC and 1.96 μgHOA/μgrBC. The absorbing properties of aerosols were characterized at multiple wavelengths (λ), and a stronger spectral dependence of absorption was observed when this site was significantly influenced by solid fuel burning. The rBC was estimated to contribute 3–16% of submicron aerosol mass. The single scattering albedo at λ = 700 nm (SSA700 nm) was significantly anti-correlated with the rBC mass fraction, but also associated with the BC mixing state. The BC incorporation/removal process therefore may play a role in modulating the radiative properties of aerosols at the site under the influence of fresh sources. Given that traffic and residential combustion of solid fuels are significant contributors of carbonaceous aerosols over Europe, these results provide important source-specific information on modeling the anthropogenic carbonaceous aerosols.